We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website.
Please click on "Accept cookies" if you agree to the setting of cookies. Cookies that do not require consent remain unaffected by this, see
cookie policy and privacy policy.
DECLINE COOKIES

Need help with a couple, also please correct me if i'm wrong

3. x=3y+2

-2 from both sides= x-2=3y

(3)x-2(3)=(3)3y=

y=3x-6

4. x=2/3y-5

+5 both sides

x+5=2/3y

(3/2)x+(3/2)5=(3/2)2/3y=

y=3/2x+7.5

5. x=y^2+8

-8 from both sides= x-8=y^2 (not sure what comes next) is it x-8^2=(y^2)^2 ???

6. x=(y+3)^2

Not sure what to do next for this one but I tried a little bit: x^2=((y+3)^2)^2=x^2=y+3 I don't know >.<

RainbowPanda Aug 21, 2018

#1**+2 **

3. f(x) = 3x + 2

Here's the way I learned it..... for f(x), write "y".... get x by itself... "swap" x and y

and for "y" write f^{-1}(x) [this notation represents the inverse ]

So we have

y = 3x+ 2

y - 2 = 3x

[y - 2] / 3 = x "swap" x and y

[x - 2 ] / 3 = y

[x -2 ] / 3 = f^{-1}(x)

BTW....swapping x and y like you did in your first step is OK, too.....!!

#4 looks good...!!!

Here's the last two

f(x) = x^2 + 8

y = x^2 + 8

y - 8 = x^2 take both roots

±√ [y -8] = x swap x and y

±√[ x - 8 ] = y

±√[x - 8] = f^{-1}(x)

f(x) = (x + 3)^2

y = (x + 3)^2 take both roots

±√y = x + 3

±√y - 3 = x swap x and y

±√x - 3 = y

±√x - 3 = f^{-1}(x)

CPhill Aug 21, 2018

#2**+2 **

Thank you, that's not quite how I learned it but maybe i'll get used to it being that way...

RainbowPanda
Aug 21, 2018